Native arbuscular mycorrhizal fungi promote the growth of Vitex cofassus seedlings in post-asphalt mining soil media - Tuheteru, Faisal Danu; Husna; Nurdin, Wiwin Rahmawati; Himawan, Ade; Tuheteru, Edy Jamal; Albasri; Mulyono, Sri; Arif, Asrianti (Journal of Degraded and Mining Lands Management, 2025)
Post-asphalt mining land is generally damaged and infertile; therefore, restoration efforts are necessary. The use of native Arbuscular Mycorrhizal Fungi (AMF) can improve plant growth and accelerate the success of restoration. This research aimed to elucidate the effect of native AMF inoculation on the growth of Vitex cofassus seedlings in greenhouse conditions. In this study, a completely randomized design was implemented with seven treatments, i.e., uninoculated (control), Racocetra crispi, Glomus intraradices, Glomus sp., Glomus sp-LW10, Glomus sp.-SW10 and Mycofer IPB (commercial AMF). The percentage of AMF colonization, plant growth, dry weight as well as P and Ca uptakes were measured after 3 months of planting. The results showed that AMF inoculation significantly increased the percentage of colonization, growth, and dry weight of shoots and total plants of V. cofassus. Mycorrhizal Inoculation Effect (MIE) ranged between 92.2% and 94.6%. Native and commercial AMF inoculation increased P and Ca uptakes in the roots and shoots of V. cofassus. There is a promising future for native AMF to be developed into a biofertilizer for restoring post-asphalt mining land in Indonesia.